Discovery and characterization of an eccentric, warm Saturn transiting the solar analog TOI-4994 - Rodríguez Martínez, Romy; Eastman, Jason D.; Collins, Karen A.; Rodriguez, Joseph E.; Charbonneau, David; Quinn, Samuel N.; Latham, David W.; Ziegler, Carl; Brahm, Rafael; Fairnington, Tyler R.; Ulmer-Moll, SolÉne; Stassun, Keivan G.; et al. (The astronomical journal, 2025)
We present the detection and characterization of TOI-4994b (TIC 277128619b), a warm Saturn-sized planet discovered by the NASA Transiting Exoplanet Survey Satellite. TOI-4994b transits a G-type star (V = 12.6 mag) with a mass, radius, and effective temperature of , , and Teff = 5640 ± 110 K. We obtained follow-up ground-based photometry from the Las Cumbres Observatory and the Antarctic Search for Transiting ExoPlanets telescopes, and we confirmed the planetary nature of TOI-4994b with multiple radial velocity observations from the Planet Finder Spectrograph, CHIRON, High Accuracy Radial velocity Planet Searcher, Fiber-fed Extended Range Optical Spectrograph, and CORALIE instruments. From a global fit to the photometry and radial velocities, we determine that TOI-4994b is in a 21.5 day eccentric orbit (e = 0.32 ± 0.04) and has a mass of , a radius of , and a Saturn-like bulk density of . We find that TOI-4994 is a potentially viable candidate for follow-up stellar obliquity measurements. TOI-4994b joins the small sample of warm Saturn analogs and thus sheds light on our understanding of these rare and unique worlds.
Gesehen am 15.07.2025